2012
DOI: 10.1073/pnas.1218606110
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Solidago altissima plants to volatile emissions of an insect antagonist ( Eurosta solidaginis ) deters subsequent herbivory

Abstract: Recent work indicates that plants respond to environmental odors. For example, some parasitic plants grow toward volatile cues from their host plants, and other plants have been shown to exhibit enhanced defense capability after exposure to volatile emissions from herbivore-damaged neighbors. Despite such intriguing discoveries, we currently know relatively little about the occurrence and significance of plant responses to olfactory cues in natural systems. Here we explore the possibility that some plants may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
102
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(120 citation statements)
references
References 40 publications
(62 reference statements)
11
102
3
Order By: Relevance
“…Recently, it was reported that a putative sex attractant of male goldenrod gall flies primed tall goldenrod for enhanced defense responses (e.g., JA production) and augmented resistance to feeding damage by goldenrod leaf beetle (35). This finding disclosed a novel type of plantinsect interaction in which the plant perceives olfactory cues from a coevolved herbivore.…”
Section: Priming For Enhanced Defense To Herbivorymentioning
confidence: 95%
“…Recently, it was reported that a putative sex attractant of male goldenrod gall flies primed tall goldenrod for enhanced defense responses (e.g., JA production) and augmented resistance to feeding damage by goldenrod leaf beetle (35). This finding disclosed a novel type of plantinsect interaction in which the plant perceives olfactory cues from a coevolved herbivore.…”
Section: Priming For Enhanced Defense To Herbivorymentioning
confidence: 95%
“…Dense outbreaks resulting in complete defoliation lead to mass exodus of adult beetles which then go on to oviposit in the soil of other patches (Morrow et al, 1989). Third, the preference of E. solidganis and the performance of Trirhabda on goldenrod clones differing in induced defenses both appear to respond in the same direction (Helms et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…But insect herbivory can have a multitude of possible effects on host plant physiology (Karban and Baldwin, 1997), and Trirhabda folivory has previously been shown to affect Solidago leaf quality (Brown and Weis, 1995). A recent study by Helms et al (2013) also demonstrates a potentially strong role of induced defenses in S. altissima, with herbivore cues eliciting a strong up-regulation of jasmonic acid production. We hypothesize the effect of high levels of folivory by Trirhabda defoliation on the reactive tissue utilized by E. solidaginis may interfere with gall induction.…”
Section: Introductionmentioning
confidence: 99%
“…How rapidly a plant detects and responds to a pathogen can make the difference between resistance and susceptibility (Greenberg 1997), and rapid detection may also be important in defense against herbivores. For example, goldenrod plants can detect sex pheromones from herbivorous flies (Helms et al 2013), and Arabidopsis responds to chemicals in the slime of herbivorous slugs (Orrock 2013) as advance warning of future herbivory. These recent discoveries exemplify that diverse and currently under-studied index cues from attackers provide information in plant-herbivore-pathogen interactions.…”
Section: Small Molecules Affect Top-down and Bottom-up Community Intementioning
confidence: 99%